Економічний механізм підвищення ефективності використання залучених коштів громадськими організаціями з метою розвитку підприємництва - Коваль, З. О.; Коваль, Я. Б.; Хом’як, Р. Л. (Видавництво Львівської політехніки, 2014)
Обґрунтовано необхідність формування економічного механізму підвищення ефективності використання залучених коштів громадськими організаціями з метою розвитку підприємництва в Україні. Проаналізовано наявний стан щодо надходження і використання залучених коштів громадськими організаціями, динаміку і структуру цих коштів. Досліджено ефективність використання цих коштів та можливості їх викoристання для розвитку вітчизняного підприємництва.Запропоновано основні аспекти побудови економічного механізму підвищення ефективності використання залучених коштів громадськими організаціями з метою розвитку підприємництва. The article substantiates the need for the formation of the economic mechanism more efficient use of raised funds community organizations to develop business in Ukraine. Are pointed out problems indicate that use of the capacity of the public and community organizations in the development of business in Ukraine, namely: low public awareness about the prestige and benefits of opening their own business; distrust of the public authorities of the executive power and local self government; low awareness of entrepreneurs and work associations; insufficient level of logistical support and professional training community organizations and passivity community organizations to involve its members, representatives, experts involved in training programs. There is also a large number of problems of the financial plan, namely the decrease in state funding of community organizations, lack of mechanism to finance their statutory activities, as well as their consumer approach to raising funds for the implementation of statutory activities and more. Other problems associated with the formal approach of some managers of state executive authorities and local authorities to implement the provisions of the current legislation, administrative documents executive authorities regulating the work to ensure the participation of public institutions in the formation and implementation of public policy, including policy development. in addition, we have a low level of business confidence in public institutions and the small number of success stories of their cooperation. Separation problems and create conditions for inefficient use of funds raised by community organizations. Also processes the receipt and use of these resources require proper balancing. The article analyzes the current state on receipt and use of funds raised by community organizations, dynamics and structure of these funds. Structure research use of the community organizations during the last three years shows that a significant portion funds raised were repaid by the state or non governmental donors unused or not reflected in the statistical reports. The efficiency of the use of funds raised by community organizations and their possible use for the development of domestic business. The basic conditions of efficiency funds community organizations, namely: establishing a dynamic and multilevel cooperation with their business, their effective support for the development of social enterprises, providing them unbiased reporting in the statistics for the full analysis of the public sector, including for the development of entrepreneurship and more. The basic aspects of building economic mechanism more efficient use of funds raised community organizations for the development of business, objective of which would be a reasonable balancing processes the receipt and use of these funds.
Economic mechanism efficiency raised funds community organizations to business development
Keywords: економічний механізм; ефективність використання коштів; залучені кошти; громадські організації; підприємництво; economic mechanism; efficiency of use of funds; raised funds; community organizations; business